Philosophies of the Transindividual: Spinoza, Marx, Freud. Issue 1 (2nd January 2018) - Balibar, Étienne
Abstract: In this contribution, Balibar follows his seminal 1993 work applying the notion of the transindividual to Spinoza's work, to produce a broader history of thinking the transindividual that brings both Karl Marx and Sigmund Freud into relation with Spinoza, devoting a section to each of these thinkers. Balibar positions the notion of the transindividual, here, as a solution to the opposing ontological errors of philosophical individualism that fails to attend to the social constitution of the individual, and the social organicism that reduces the individual to the effect of larger forces. For Balibar, following Gilbert Simondon, the individual is to be understood as always already extending beyond themselves.